Polish-English Terminological Equivalence in the Language of Politics - Feder, Marcin (Folia Scandinavica Posnaniensia, 2007)
In the present study we put forward a translation method that would help ensure the proper rendering of Polish political terminology into English (or any other language since the tenets of this method are universal and can be applied to any pair of languages). The translation procedure is based on findings of Barbara Z. Kielar. We also present the classification of equivalents that are obtained after applying the method. This is followed by considerations on the possibility of attaining particular types of terminological equivalence and an appeal that the presented method be applied universally in order to improve the quality of political translations produced in Poland. A sample Polish-English glossary of political terms compiled on the basis of the advocated method is enclosed as the “Appendix”.